2017
DOI: 10.1161/strokeaha.116.015439
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypokalemia and Supraventricular Ectopy Increases the Risk of Stroke in Community-Dwelling Subjects

Abstract: Background and Purpose-Stroke is independently associated with the common conditions of hypokalemia and supraventricular ectopy, and we hypothesize that the combination of excessive supraventricular ectopic activity and hypokalemia has a synergistic impact on the prognosis in terms of stroke in the general population. Methods-Subjects (55-75 years old) from the Copenhagen Holter Study cohort (N=671) with no history of atrial fibrillation or stroke were studied-including baseline values of potassium and ambulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Our results align with existing research that suggests that hypokalemia (chronic exposure) is associated with a higher risk of ischemic stroke. Among diuretic users [12], general population [14], and a treated hypertensive population [15], hypokalemia was associated with a 2.5-, 2.1-, and 2-fold higher risk of ischemic stroke, respectively. On the other hand, in a general population [13], both K levels between 4.3-8.4 mmol/L and a per mmol/L increase in K levels were associated with 1.3-fold higher risk of ischemic stroke.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results align with existing research that suggests that hypokalemia (chronic exposure) is associated with a higher risk of ischemic stroke. Among diuretic users [12], general population [14], and a treated hypertensive population [15], hypokalemia was associated with a 2.5-, 2.1-, and 2-fold higher risk of ischemic stroke, respectively. On the other hand, in a general population [13], both K levels between 4.3-8.4 mmol/L and a per mmol/L increase in K levels were associated with 1.3-fold higher risk of ischemic stroke.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…To determine the short-term risk associated with dyskalemias, we also assessed the association of time-updated dyskalemias (acute exposure) with ischemic stroke where we observed that hyperkalemia (and higher levels of K) was associated with a lower risk of ischemic stroke. Previous studies have hypothesized that hypokalemia might be a marker of increased RAAS activity [28], and an increased activity in systemic and cerebral RAAS system could potentiate the effect of a stroke, by resulting in more extensive neurologic damage and neurologic deficits [14]. This may explain the association of hypokalemia (chronic exposure) with a higher risk of ischemic stroke.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that both high and low serum potassium levels were associated with mortality in patients with cardiovascular disease [9], even mild or moderate abnormality increased the risks of morbidity and mortality in cardiovascular disease patients as well [10]. The association of abnormal levels of serum potassium with morbidity and mortality of stroke in the general population has also been reported by several recent studies [11, 12]. However, few studies have focused on the connection between serum potassium and stroke outcome in patients with acute ischemic stroke (AIS) or transient ischemic attack (TIA) after treatment.…”
Section: Introductionmentioning
confidence: 97%
“…Mild hypokalemia is generally asymptomatic; however, severe hypokalemia might cause respiratory depression, paralytic ileus, and life-threatening cardiac arrhythmias [ 1 , 2 , 3 , 4 ]. Additionally, it has been reported that a low serum potassium level is associated with mortality and morbidity [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ] in patients with cardiovascular disease, renal conditions, and others. Thus, it is important to identify or review the causes of hypokalemia to prevent or promptly and appropriately manage the disorder.…”
Section: Introductionmentioning
confidence: 99%